VALIDATION OF THE SELF-MOTIVATION SCALE: A STUDY OF ITS RELATIONSHIP WITH AUTHENTIC LEADERSHIP AND WORK ENGAGEMENT - MS. R DEEPA, DR. R ANAND (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Authentic leadership and work engagement are crucial for organizational success, yet the role of self-motivation remains underexplored. This study validated a self-motivation scale and examined its relationship with authentic leadership and work engagement in manufacturing organizations. Exploratory factor analysis revealed a four-dimensional structure with good construct validity. Structural equation modelling showed that self-motivation was positively associated with work engagement, and authentic leadership had a significant positive impact on both. However, self-motivation didn't significantly mediate the relationship between authentic leadership and work engagement. This study's main focus is validating the self-motivation scale, establishing it as a multifaceted construct with empirical validity. By doing so, it contributes to applied psychology and psychometrics, shedding light on self-motivation's complex role in leadership-engagement dynamics. The research also highlights self-motivation's potential to independently predict job performance, emphasizing the importance of precise motivational construct validation.